ACEH CONFLICT RESOLUTION BY THE GOVERNMENT OF INDONESIA - Zulhilmi; Ady Muzwardi (JIP (Jurnal Ilmu Pemerintahan) : Kajian Ilmu Pemerintahan dan Politik Daerah, 2016)
Aceh peace is a new dynamic on the resolution of conflicts in the region. Eight years have passed and the agreement was signed by the Free Aceh Movement (GAM) and the Indonesian Government, while the MoU (Memorandum of Understanding) agreed in 2005. The signing of the MoU symbolically ends Aceh conflict which is prolonged for three decades. Moreover the notable occurance that leads to the weakening of GAM strength is that by December 26, 2004 earthquake and tsunami has devastated the communities in terms of infrastructure and superstructure. While spirit to rebuild Aceh after the disaster emerged, amount of aid coming in the country from as well as foreign institutions such as NGO. The government of Indonesia took this chance to develop Aceh once again and approach GAM to release the tense, to take the path of peace. The government efforts succeed by personalized approach to one of the central figures of GAM. The conflict in Aceh reflects that lobbying skill from the government of Indonesia against GAM is quite excellent. To notice the reconstruction of Aceh peace agreement before, the Cessation of Hostility Agreement (COHA) initiated by the Henry Dunant Center (HDC) stalled. The struggle embodied in the MoU agreement which is initiated by the Crisis Management Initiative (CMI) actually formed by former Finnish President Martti Ahtisaari. While it is done further implementation is left to the Aceh Monitoring Mission (AMM) led by Pieter Feith. In this mission AMM successfully carry out their duties in accordance with the agreement so that it runs alltogether. AMM ended its duties on December 15, 2006 and successfully reconcile the peace process (AMM: 2006). Furthermore, Indonesian Government gives freedom of democracy actively for Aceh and GAM combatants. Troop’s withdrawal process also the destruction of non-organic military and police weapons of the GAM runs smoothly. Then the GAM combatants reintegrate into society, this task successfully executed by AMM. Furthermore, the Government implements the sustainability of the peace process systematically. Implementation of this peace process is necessary because people of Aceh are already saturated with conflict that endured so long. The people hope this peace could maintain significant and permanent. Fortunately all parties are able to hold theirselves up to prevent new conflicts. Above all, Aceh peace is also a very elegant example as a process of consensus building and conflict resolution models. Aceh peace could become a reference for other regions and countries in the world which is also facing separatist conflict issue. Moreover, Aceh peace could also sinergically perform post-tsunami reconstruction of the area. The Government creates the Rehabilitation and Reconstruction Agency (BRR) to reconstruct the area after the tsunami disaster. This peace model could also reintegrate and reconcile thw ex-combatant to back mingling with the public. Democratic process in Aceh is also running well, starting with local elections on December 11, 2006. Currently Aceh is very pleasant city for living and we expect peace in Aceh could maintain eternally.